A virulence-associated small RNA MTS1338 activates an ABC transporter CydC for rifampicin efflux in Mycobacterium tuberculosis - Singh, Saumya; Dutta, Tanmay (Frontiers in Microbiology, 2024)
The efficacy of the tuberculosis treatment is restricted by innate drug resistance of Mycobacterial tuberculosis and its ability to acquire resistance to all anti-tuberculosis drugs in clinical use. A profound understanding of bacterial ploys that decrease the effectiveness of drugs would identify new mechanisms for drug resistance, which would subsequently lead to the development of more potent TB therapies. In the current study, we identified a virulenceassociated small RNA (sRNA) MTS1338-driven drug efflux mechanism in M. tuberculosis.The treatment of a frontline antitubercular drug rifampicin upregulated MTS1338 by >4-fold.Higher intrabacterial abundance of MTS1338 increased the growth rate of cells in rifampicintreated conditions. This fact was attributed by the upregulation of an efflux protein CydC by MTS1338. Gel-shift assay identified a stable interaction of MTS1338 with the coding region of cydC mRNA thereby potentially stabilizing it at the posttranscriptional level. The drug efflux measurement assays revealed that cells with higher MTS1338 abundance accumulate less drug in the cells. This study identified a new regulatory mechanism of drug efflux controlled by an infection-induced sRNA in M. tuberculosis.